Analysis of the "Nipkow Disk" Phenomenon in Public Opinion Dissemination - Hou, Dun (Transactions on Social Science, Education and Humanities Research, 2024)
The "Nipkow Disk," invented by Paul Nipkow, scans and transmits images through the combination of apertures and coils. When applied as a model in communication theory, it provides a new perspective on the complexity of information dissemination. This paper explores the relationship between the "Nipkow Disk" phenomenon and public opinion dissemination, proposing that public opinion spreads not linearly but through a series of virtual nodes, such as individuals, media, or organizations, which play a crucial role in the process. These nodes form a complex network structure, where public opinion spreads in a line-by-line scanning process, fermenting rapidly and gradually revealing the full picture.